Virome diversity shaped by genetic evolution and ecological landscape of Haemaphysalis longicornis - Run-Ze Ye; Yu-Yu Li; Da-Li Xu; Bai-Hui Wang; Xiao-Yang Wang; Ming-Zhu Zhang; Ning Wang; Wan-Ying Gao; Cheng Li; Xiao-Yu Han; Li-Feng Du; Luo-Yuan Xia; et al. (Microbiome, 2024)
Abstract Background Haemaphysalis longicornis is drawing attentions for its geographic invasion, extending population, and emerging disease threat. However, there are still substantial gaps in our knowledge of viral composition in relation to genetic diversity of H. longicornis and ecological factors, which are important for us to understand interactions between virus and vector, as well as between vector and ecological elements. Results We conducted the meta-transcriptomic sequencing of 136 pools of H. longicornis and identified 508 RNA viruses of 48 viral species, 22 of which have never been reported. Phylogenetic analysis of mitochondrion sequences divided the ticks into two genetic clades, each of which was geographically clustered and significantly associated with ecological factors, including altitude, precipitation, and normalized difference vegetation index. The two clades showed significant difference in virome diversity and shared about one fifth number of viral species that might have evolved to “generalists.” Notably, Bandavirus dabieense, the pathogen of severe fever with thrombocytopenia syndrome was only detected in ticks of clade 1, and half number of clade 2-specific viruses were aquatic-animal-associated. Conclusions These findings highlight that the virome diversity is shaped by internal genetic evolution and external ecological landscape of H. longicornis and provide the new foundation for promoting the studies on virus-vector-ecology interaction and eventually for evaluating the risk of H. longicornis for transmitting the viruses to humans and animals. Video Abstract